Evaluasi Penyajian Laporan Keuangan Pada UD. Subur Jaya Meubel Berdasarkan Standar Akuntansi Keuangan Entitas Mikro, Kecil, Dan Menengah (SAK EMKM) - Catur Kumala Dew, Novi Syahputra Titin Ruliana (EKONOMIA, 2020)
This study aims to evaluate the presentation of items in the financial statements at UD. Subur Jaya Meubel based on SAK EMKM 2018 and the formulation of the problem in this study is whether the presentation of items in the financial statements at UD. Subur Jaya Meubel is appropriate based on SAK EMKM 2018.The theory used in this research is financial accounting. The hypothesis put forward is the presentation of items in the financial statements at UD. Subur Jaya Meubel is incompatible with SAK EMKM 2018.The analytical tool used in this study is a comparative descriptive method, which compares the presentation of the structured account placement in the financial statements based on SAK EMKM with UD. Subur Jaya Meubel uses the Champion formula method.The results showed that the suitability of structured account placement in the financial statements according to UD. Subur Jaya Meubel is not suitable according to SAK EMKM 2018 with a criterion value of 33%. The conclusion of this research is the presentation of financial statements at UD. Subur Jaya Muebel is not in accordance with the provisions of SAK EMKM 2018 because of UD. Subur Jaya Meubel did not prepare and present financial position reports and notes to the financial statements so that the hypothesis was accepted.